Exocrine pancreatic response to the venom of the scorpion, Tityus trinitatis. Issue 8 (August 1977) - Bartholomew, C; Murphy, J J; McGeeney, K F; Fitzgerald, O
Abstract : This paper records for the first time the exocrine pancreatic response to scorpion venom, in this case that of Tityus trinitatis, a scorpion endemic in Trinidad. The crude venom injected intravenously into fasting anaesthetised dogs induced a secretion of the exocrine pancreas. The secretion evoked was rich in enzymes.